(untitled) (Medico Legal Update, 2021)
Background: This study was conducted to develop a training program simulating multidrug-resistant organism infection control for nurses and to verify its effectiveness. Method: This was a randomized, control-group, pretest-posttest design study carried out with a total of thirty-one nurses. A general lecture on theories was provided to the control group, while the developed simulation training program was implemented for the experimental group. Result: The results showed that the experimental group who received the multidrug-resistant infection control simulation training program recorded higher infection control performance than the control group who received lecture-based training (p=.029). However, there was no statistically significant difference in infection control fatigue and job stress between the two groups. Conclusion: It was found that the simulation training program is an effective intervention that can improve the performance of infection control. Repeated research on diverse variables is necessary in the future in order to continuously measure the effectiveness of the simulation training program.